Optimasi Daya Pada Panel Surya Dengan Solar Tracker System Dual Axis Menggunakan Metode Fuzzy Logic Controller - Rizqi Andika Prasetyo; Arnisa Stefanie; Wilma Nurrul Adzillah (Peneliti.net, 2021)
One of the alternative energies that almost includes the criteria for being safe for the environment is solar energy. Fuzzy logic mapping is carried out on the matlab using the sugeno fuzzy method with a system that has 4 inputs and 2 outputs. Fuzzy logic is a method used for solar trackers in order to optimize the power on solar panels. Membership function for LDR 1, LDR 2, LDR 3 and LDR 4 values ​​are Low (0-400), Medium (100-900), and High (600-1023), respectively. Comparison between static solar panels and dual axis solar tracker solar panels results in power optimization obtained by 27.75%.